THE QUALITY IMPROVEMENT TOWARDS MINIMIZING GRILLE BASE PRODUCTS DEFECTS WITH SIX SIGMA APPROACH - Indah Pratiwi, Annisa; Hakim, Afif; Murnawan (International Journal of Psychosocial Rehabilitation, 2020)
Quality is an essential part of the company must be fulfilled to provide customer satisfaction. In the industrial revolution era 4.0, quality becomes an indicator of companies in competing with their competitor. The one automotive company in Karawang is processing in improving its product quality, especially in the painting process. The quality condition of Grille Base products have a high enough product defect ratio, namely 42.79% butsu defects (spots), 25.45% hajiki defects (cissing), 18.93% yarn defects (fiber), 4.66% orange peel defects, 4.27% sagging defects, 2.47% gross area defects, 0.68% blister defects, 0.58% thin paint defects, and 0.16% frosted defects (low glossy). The sigma score in the painting process is 2.8 sigmas with 84432.21 DPMO. This condition indicates that it needs immediately improved quality. The concept used is the six sigma approach with the DMAIC cycle (Define, Analyze, Measure, Improve, and Control). This research focuses on increasing the score of sigma in the painting process. FTA use for analyzing the improvements and FMEA identification used to determine the appropriate improvement. The results of improvements result in 2.9 sigmas with DPMO 71008, which means that there are millionth opportunities may facing 71008 products failures.